IPO Underpricing and Its Dynamic Changes in Chinese A-share Market: An Empirical Analysis from 1996 to 2015 - HU, HONGXIN (2016)
By conducting multiple linear regression analysis on 1645 samples of IPOs in Chinese A-shares stock market, this dissertation illustrates the determinants of IPO underpricing in Chinese IPO market for period 1996 to 2015. Specifically, following the important reforms in the market, the paper also identify the dynamic change in both IPO underpricing level and the factors affects the underpricing in five subperiods of for the past 20 years. The finding of this paper shows IPO underpricing in China is not only caused by factors indicated in conventional theories such as winner’s curse effect and signalling effect, but also related to unique characteristics in the market like IPO quota restriction and state ownership. However, the result of subperiod analysis implied that as IPO reforms has been promoted, the factors of unique characteristics of Chinese IPO market become less important and the underpricing level decrease significantly, showing the market is transforming close to western market and become more mature.